Understanding individual perceptions in workplace safety practices background - Xu, Qinghui (2015)
With more emphasis placed on workplace safety in recent decades, there is an increasing interest in research in this area. In particular, the focus of such research has been on uncovering the reasons behind why workers engage in at-risk behaviour at the workplace. This project aims to improve workplace safety by understanding workers’ behaviour via two behavioural models, Behaviour-Based Safety and the Theory of Planned Behaviour. Supported by the two theories, research was conducted in three phases to uncover the underlying reasons for workers’ engaging in at-risk behaviour. Surveys and interview, coupled with field observations were conducted to find out the prevailing workplace safety culture at two participating companies, Cameron (Singapore) and Yongnam Engineering. The report will discuss results from Phase I of the study (a survey of workers’ perception of workplace safety) and the conduct of Phase II of the study, namely one-on-one interview sessions with workers and field observations at the two participating companies. The results from Phase II of the study led to suggested intervention measures in Phase III to improve workplace safety. Ultimately, the research project aims to provide a feedback loop that can identify and correct safety gaps present in various industries.